Identification of groundwater potential zones in the Rabigh-Yanbu area on the western coast of Saudi Arabia using remote sensing (RS) and geographic information system (GIS) - Alharbi, Talal; Abdelrahman, Kamal; El-Sorogy, Abdelbaset S.; Ibrahim, Elkhedr (Frontiers in Earth Science, 2023)
The groundwater potential zones in the Rapigh-Yanbu area, on the west coast of Saudi Arabia, were evaluated using remote sensing and geographic information system data leading to the establishment of major watershed development and management strategies. Many factors, including slope, drainage density, land use, geology, lineament density, elevation, yearly precipitation, and soil type distribution, affect the hydrogeological characteristics of coastal aquifers. The Rabigh-Yanbu coastline groundwater potential zones were located and mapped using these characteristics. The annual precipitation rate is categorized into 2–28 mm, 29–52 mm, 53–76 mm,77–107 mm, and 108–164 mm within the study area. The highest elevation was ordered with the lowest rank of 1, while the lowest elevation was given the highest rank of 5. Slopes of 0°–9° were present in the majority of the study region, while slopes of 9°–63° were present in the northwest. Based on the slope, the research area was separated into five classes; 0-3o; 4-9o; 10–16o; 17–25o; 26–63o. Based on the drainage density map; 0–0.36 km2, 0.37–0.53 km2, 0.54–0.73 km2, 0.74–1.32 km2, 1.33–3.31 km2. The majority of the fractures trended NE–SW and NW–SE. A map of lineament density was made using the line density method. This map makes it obvious that the region was divided into five classes; 0–0.02 km2, 0.03–0.08 km2, 0.09–0.13 km2, 0.14–0.2 km2, and 0.21–0.34 km2. The classification of soil types in the study region into four classes such as clay loam, clay, sandy clay, and loam. Accordingly, the clay soil was ranked 1, while the loam soil was given the highest rank of 4. The Precambrian rocks had low groundwater potential because of their reduced porosity and were ranked 1, while Quaternary deposits had a high porosity and good groundwater potential and were given a high rank of 3. According to the likelihood of groundwater supply, the area is divided into four categories: very good, good, moderate, and poor. The area with very good groundwater potential covered 1,384 km2, while the area with good groundwater potential covered 30,498 km2, according to the findings. The study area had 34,412 km2 of somewhat appropriate land for groundwater development. In contrast, 1,734 km2 of the study area is scarce. The best zones featured the lowest slopes, the least number of lineaments, and the most drainage. The lineaments, which serve as the main conduits for groundwater flow and storage, have significant levels of groundwater recharge capacity in the study area. Managing groundwater according to these identified potential zones will maximize their benefits and increase the groundwater yield. This will help in creating new agricultural, urban, and industrial communities in this strategic area and contribute toward achieving the goals of Saudi Vision 2030.